Peningkatan Kemampuan Mengenal Nilai Tempat melalui Media Pembelajaran Blok Dienes pada Siswa Gangguan Spektrum Autisme - Pujangkoro, Anang; Nurhastuti, Nurhastuti; Rahmahtrisilvia, Rahmahtrisilvia; Taufan, Johandri; Nasri, Yosa Yulia (Universitas Syiah Kuala, 2025)
This study aims to improve the ability to recognize place value concepts among a sixth-grade student with Autism Spectrum Disorder (ASD) at SLB Negeri Tebo through the use of Dienes blocks as concrete learning media. The initial assessment showed that the student was able to recognize numbers but experienced difficulties in identifying unit, tens, and hundreds place values, with a performance score of only 20%, far below the schools KKTP standard of 75%. This classroom action research employed two cycles consisting of planning, action, observation, and reflection. Data were collected through structured observation to document learning behaviors, performance tests at the end of each meeting, and documentation to support qualitative findings. The data were analyzed descriptively by comparing test results across cycles and interpreting behavioral changes based on observation notes. The findings indicate a gradual improvement from cycle I to cycle II. In cycle I, although the student showed increased interest in using Dienes blocks, mastery of the concept had not yet reached the expected level. Significant improvement occurred in cycle II, marked by the students ability to independently arrange units, tens, and hundreds, and correctly solve place value tasks. The final score reached 93.3%, exceeding the KKTP threshold. The results demonstrate that Dienes blocks effectively support students with ASD in understanding abstract mathematical concepts by providing concrete, visual, and structured learning experiences.